"FORMULATION AND EVALUATION OF MORONIC ACID LOADED TRANSDERMAL PATCHES" - RANI, RITU; KAUR, TARANJIT; SINGH, AJEET PAL; SINGH, AMAR PAL (International Journal of Current Pharmaceutical Research, 2021)
Objective: To prepare Transdermal patches of Moronic acid along with various polymers for controlled release action. Methods: Suitable method such as Solvent Casting Technique of Film Casting Technique are used for the preparation of Transdermal patch. Results: The prepared Transdermal patches were transparent, smooth, uniform and flexible. The method adopted for the preparation of the system was found satisfactory. Conclusion: Various formulations were developed by using hydrophilic and hydrophobic polymers like HPMC E5 and EC respectively in single and combinations by solvent evaporation technique with the incorporation of penetration enhancer such as dimethylsulfoxide and dibutyl phthalate as plasticizer. Formulation F7 containing an equal ratio of HPMC E5: EC (5:5) showed maximum and sustained release of 86.814±0.262 within 24 h. Kinetic models were used to confirm the release mechanism of the formulations. Moronic acid release from the patches F1 to F7 followed non Fickian diffusion rate controlled mechanism.